Financial reporting of Islamic banks in Bangladesh: basis of regulatory compliance - Rahman, Mohammad Sahabuddin; Islam, Md. Robiul; Muhammad, Junaina; Ali @ Hamid, Mass Hareeza; Bashir, Md Abdul (Publications International Lahore, 2018)
There is a worldwide trend to adopt the international financial reporting standards (IFRS) but Islamic banking companies in Bangladesh are required to follow different rules and regulations. These banks should follow more regulatory formalities than the conventional ones. The Bangladesh Financial Reporting Standards (BFRS) adopted the International Financial Reporting Standards (IFRS) in 2000. Since then, the regulator in Bangladesh has initiated the Sharia governance framework from regulatory and non-regulatory aspects. This study considered the annual report of 8 Islamic banks in Bangladesh in 2015 and tried to identify the requirements in preparing the financial reports under Islamic Shariah and to show the compliance status of these banks. The average compliance rate with the requirements was found to be 88.11%. It is recommended that in complying the requirements of the financial reports, Bangladesh Bank may modify BRPD Circular No. 15/2009 that will be helpful for banks to prepare financial reports conveniently.